1998
DOI: 10.1038/sj.bjp.0702106
|View full text |Cite
|
Sign up to set email alerts
|

The signal transduction mechanism involved in kazinol B‐stimulated superoxide anion generation in rat neutrophils

Abstract: 1 In this study, the underlying mechanism of stimulation of respiratory burst by kazinol B, a natural isoprenylated¯avan, in rat neutrophils in vitro was investigated. 2 Kazinol B concentration-dependently stimulated the superoxide anion (O 2 ⋅7 ) generation, with a lag but transient activation pro®le, in neutrophils but not in a cell-free system. The maximum response (13.2+1.4 nmol O 2 ⋅7 10 min 71 per 10 6 cells) was observed at 10 mM kazinol B.3 Pretreatment of neutrophils with phorbol 12-myristate 13-aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The mixture was centrifuged at 20 000 g for 20 min, the resultant pellet were resuspended in 1.5 mL of pyridine and kept at 80 °C for 1.5 h to extract formazon. The mixture was centrifuged at 10 000 g for 10 min and the absorbance of the formazon was determined spectophotometrically (DU 640B Spectrophotometer, Beckman Coulter Inc.) at 540 nm [34]. The amount of reduced NBT was calculated using the following formula: …”
Section: Methodsmentioning
confidence: 99%
“…The mixture was centrifuged at 20 000 g for 20 min, the resultant pellet were resuspended in 1.5 mL of pyridine and kept at 80 °C for 1.5 h to extract formazon. The mixture was centrifuged at 10 000 g for 10 min and the absorbance of the formazon was determined spectophotometrically (DU 640B Spectrophotometer, Beckman Coulter Inc.) at 540 nm [34]. The amount of reduced NBT was calculated using the following formula: …”
Section: Methodsmentioning
confidence: 99%
“…The signal transduction mechanism involved in superoxide anion generation, in response to chemical substances, has been extensively studied [19], and some of Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Several bioactive substances including coumarins, polyphenols, alkaloids, glycosides, flavonoids, lignans and diterpenes were isolated from bioassay‐guided fractionation of the extracts of these plants (Takasugi et al , ; Gunatilaka et al , ; Ikuta et al , ; Kato et al , ; Dehmlow et al , ; Fang et al , ; Shibano et al , ; Son et al , ; Zhang et al , ; Mei et al , ). Some members of these compounds have been reported to possess antiosteoporotic, antidiabetic, antioxidant, antitumoural, antimicrobial, antiplatelet, antiinflammatory and antityrosinase properties (Takasugi et al , ; Lin et al , ; Ko et al , ; Shibano et al , ; Wang et al , ; Lee et al , ; Zhang et al , ; Zheng et al , ; Zhou et al , ); for example, broussochalcone A inhibited both formylmethionyl‐leucyl‐phenylalanine (fMLP)‐ and phorbol 12‐myristate 13‐acetate (PMA) induced respiratory burst in neutrophils (Wang et al , ), broussonin C exhibited inhibitory activities against both the monophenolase and diphenolase actions of tyrosinase (Baek et al , ), and broussonin A showed estrogenic and transcriptional activity (Lee et al , ).…”
Section: Introductionmentioning
confidence: 99%